Amplifying cancer treatment: advances in tumor immunotherapy and nanoparticle-based hyperthermia - Zhang, Yi; Li, Zheng; Huang, Ying; Zou, Bingwen; Xu, Yong (Frontiers in Immunology, 2023)
In the quest for cancer treatment modalities with greater effectiveness, the combination of tumor immunotherapy and nanoparticle-based hyperthermia has emerged as a promising frontier. The present article provides a comprehensive review of recent advances and cutting-edge research in this burgeoning field and examines how these two treatment strategies can be effectively integrated. Tumor immunotherapy, which harnesses the immune system to recognize and attack cancer cells, has shown considerable promise. Concurrently, nanoparticle-based hyperthermia, which utilizes nanotechnology to promote selective cell death by raising the temperature of tumor cells, has emerged as an innovative therapeutic approach. While both strategies have individually shown potential, combination of the two modalities may amplify anti-tumor responses, with improved outcomes and reduced side effects. Key studies illustrating the synergistic effects of these two approaches are highlighted, and current challenges and future prospects in the field are discussed. As we stand on the precipice of a new era in cancer treatment, this review underscores the importance of continued research and collaboration in bringing these innovative treatments from the bench to the bedside.